Hudson Bay, or, Everyday life in the wilds of North America during six years' residence in the territories of the Hon. Hudson Bay Company - Ballantyne, R. M. (Robert Michael), 1825-1894. (London, 1879)
Preservation photocopy. Mode of access: Internet.